In vitro metal ion release and biocompatibility of amorphous Mg67Zn28Ca5 alloy with/without gelatin coating - Chan, Wing Yue (2016)
Amorphous zinc-rich Mg–Zn–Ca alloys have exhibited good tissue compatibility and low hydrogen evolution in vivo. However, suboptimal cell–surface interaction on magnesium alloy surface observed in vitro could lead to reduced integration with host tissue for regenerative purpose. This study aims to improve cell–surface interaction of amorphous Mg67Zn28Ca5 alloy by coating a gelatin layer by electrospinning. Coated/uncoated alloys were immersed and extracted for 3 days under different CO2. The immersion results showed that pH and metal ion release in the alloy extracts were affected by gelatin coating and CO2, suggesting their roles in alloy biocorrosion and a mechanism has been proposed for the alloy–CO2 system with/without coating. Cytotoxicity results are evident that gelatin-coated alloy with 2-day crosslinking not only exhibited no indirect cytotoxicity, but also supported attachment of L929 and MG63 cell lines around/on the alloy with high viability. Therefore, amorphous Mg67Zn28Ca5 alloy coated with gelatin by electrospinning technique provides a useful method to improve alloy biocompatibility.